The Philosophy of Security in the Globalizing Culture System - Kononov, Sergey Viktorovich; Zhukov, Artem Vadimovich (Journal of History Culture and Art Research, 2020)
The article presents an attempt to analyze modern theories of security within Western philosophical concepts. The authors’ goal is to conceptualize modern philosophical notions of security. To reach it, the authors use the following methodology: phenomenological and hermeneutical analysis of texts, as well as historical, cultural, and comparative analysis. The novelty of the research lies in the fact that the modern trends of development of the philosophy of safety here are connected with the drive to conceptualize the essence of security as a sophisticated and complex system, with its structure including several subsystems, such as the human being, the society, the authorities, and the international community. The authors' reason that the synthesis of these concepts and their ideas gives ground for an integral concept of security. It could take into account the points of concepts that indicate the material, ontological content of threats from the outer, globalizing world, and the mental content of threats constructed by consciousness, responding to the increasing influence of modern informatization and virtualization processes. According to the authors, within the integral security concept, and based on the complementarity principle, it is necessary to synthesize the ideas of the national-state concept of security, the “international community” concept, the “soft power” concept, and the postmodern concepts. Such concepts, dedicated to the modern threats, regard the possibility of protection from them only within the framework of the collective security system that takes into account the defense from external and mental threats to the individual, society, and the state.